Sistem Informasi Lembaga Sertifikasi Profesi P-1 Politeknik Negeri Ketapang Berbasis WEB - Darmanto, Darmanto; Akhmad, Pusparini; Pratomo Sibuea, Budi; Nurdianita, Nurdianita (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
In an effort to prepare competitive and superior human resources, vocational higher education providers are expected to equip their students with competencies that are recognised by the industrial world. One of the institutions given the task of organising professional certification activities is the Professional Certification Agency (LSP) which obtained a licence from the National Professional Certification Agency (BNSP). Politap is a tertiary institution in Ketapang Regency that is licensed as a Professional Certification provider for students from 8 study programs in Politap. Based on observations made by LSP-P1 Politap in administrative management, starting from participant registration to the implementation of competency tests is still done manually, so that LSP-P1 Politap administrators often experience difficulties in the process of preparing files when implementing certification. The purpose of this research is to create a web-based information system that is built using the Laravel framework. The method used in making the Politap LSP-P1 information system uses Agile Software Development. Meanwhile, to ensure that the information system is successfully built, system testing is carried out using the black box testing method. The results of the research are in the form of an information system that can help the process of managing the administration of competency test participant data, scheduling, documentation and facilitate the preparation of reports on the results of the competency test by LSP-P1 Politap.